2023
DOI: 10.1159/000530085
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity among Primary Health Care Physicians and Its Impact on Counseling Practices

Abstract: <b><i>Introduction:</i></b> Physical inactivity has been linked to various noncommunicable diseases and their related health problems. As primary health care physicians (PHCPs) play a crucial role in promoting health and preventing disease, this study aims to determine the extent of physical inactivity among PHCPs and its impact on their counseling practices. <b><i>Methods:</i></b> A cross-sectional study was conducted across all primary health care centers in Qa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 31 publications
1
10
0
Order By: Relevance
“…From the 62 articles included, 48.4% ( n = 30) employed a qualitative design [ 43 , 46 , 48 , 49 , 54 , 55 , 58 , 60 , 62 , 65 , 67 , 68 , 71 , 76 – 80 , 83 , 84 , 87 89 , 92 97 , 99 ], 37.1% ( n = 23) a quantitative design [ 42 , 44 , 45 , 52 , 53 , 57 , 61 , 63 , 64 , 66 , 69 , 72 75 , 81 , 82 , 85 , 91 , 98 , 100 – 102 ], and 14.5% ( n = 9) a mixed-methods study design [ 47 , 50 , 51 , 56 , 59 , 70 , 86 , 90 , 103 ]. The majority of the studies (87.1%) were conducted in high income countries (United Kingdom, n = 15; Canada, n = 9; USA, n = 7; other countries, n = 23), while only 12.9% were conducted in upper middle income countries (Brazil, n = 4; Thailand, n = 2; Jordan, n = 1; Turkey, n = 1), according to the categorization of the World Bank [ 104 ].…”
Section: Resultsmentioning
confidence: 99%
“…From the 62 articles included, 48.4% ( n = 30) employed a qualitative design [ 43 , 46 , 48 , 49 , 54 , 55 , 58 , 60 , 62 , 65 , 67 , 68 , 71 , 76 – 80 , 83 , 84 , 87 89 , 92 97 , 99 ], 37.1% ( n = 23) a quantitative design [ 42 , 44 , 45 , 52 , 53 , 57 , 61 , 63 , 64 , 66 , 69 , 72 75 , 81 , 82 , 85 , 91 , 98 , 100 – 102 ], and 14.5% ( n = 9) a mixed-methods study design [ 47 , 50 , 51 , 56 , 59 , 70 , 86 , 90 , 103 ]. The majority of the studies (87.1%) were conducted in high income countries (United Kingdom, n = 15; Canada, n = 9; USA, n = 7; other countries, n = 23), while only 12.9% were conducted in upper middle income countries (Brazil, n = 4; Thailand, n = 2; Jordan, n = 1; Turkey, n = 1), according to the categorization of the World Bank [ 104 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the western region of Saudi Arabia, another study indicated that 65% of physicians were classified as physically inactive, with only 35% reporting engagement in any sportsrelated activity [11]. These findings underscore the importance of addressing the issue of physical activity within the medical community [12].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the fact that the majority of surveyed podiatrists prioritize exercise as the primary treatment, no changes would be recommended, as they are acting correctly in this regard. It has been demonstrated that physicians who engage in physical activity and dedicate at least 3 min per visit to providing exercise advice achieved a 25% adherence rate among their patients to these recommendations [ 12 ]. This finding reinforces the notion that physicians who do not adopt healthy behaviors are less likely to advise their patients on healthy lifestyle habits.…”
Section: Discussionmentioning
confidence: 99%
“…However, one of the most important predictors of PCPs providing health promotion counseling is PCPs’ own health and active behaviors, as it is difficult to encourage behaviors that one does not engage in [ 13 ], even though a considerable number of studies analyze the health-promoting PA or inactivity of various social groups in the context of their weight or BP [ 14 , 15 , 16 ]. Unfortunately, there is not much scientific research on PCPs’ BP or BMI and their PA [ 17 , 18 , 19 , 20 , 21 , 22 , 23 ], and even fewer studies have examined the relationship between PCPs’ PA and health indicators [ 24 ].…”
Section: Introductionmentioning
confidence: 99%